EXPERIENTIAL MARKETING, SALES PROMOTION, AND PRICE DISCOUNT ANALYSIS ON ELECTRONIC PRODUCT BUYING DECISION - baruno, agustiawan djoko; Sulistydea, Novriza Annisa (Universitas Dr. Soetomo, 2021)
This research intended to verify as well as analyze the connection of experiential marketing, sales promotion and price discount variables to electronic product buying. Population of the research are consumers of Miami Electronik Surabaya. Research sampling use purposive sampling technique with some specific thought then gained 65 respondents analysis method that used here is multiple linear regression with tool aid of SPSS version 2.0 application. Based on the study research either simultaneously and partially can be known that there are positive and significant effect among variables of experiential marketing, sales promotion and price discount to electronic product buying it can be verified with f-test show that significant value is smaller than 0,005 that is 0,025 and partially, Experiential Marketing have influence on buying decision, that is proved with t-test which show that significant value smaller than 0,05 namely 0,004 next to Sales Promotion partially influenced buying decision, this phenomenon verified with t-test which show that significant value smaller as 0,05 that is 0,007 then partially, Price Discount influenced on buying decision, this is proved with t-test show that significant value is smaller than 0,05 of 0,001.